IMPLEMENTASI NILAI-NILAI PANCASILA MELALUI PERMAINAN TRADISIONAL PADA MURID SD NEG. 137 KAEMBA KAB. MAROS - Darmawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The purpose of this research is to describe the implementation of Pancasila values through traditional games in students of SD Neg. 137 Inpres Kaemba Kab. Maros. The research was carried out at the Neg. 137 Inpres Kaemba Kec. Marusu Kab. Maros. The type of research used is qualitative research with methods of observation, interview, and documentation. Implementation of the values of Pancasila through traditional games in the students of SD Neg. 137 Inpres Kaemba Kab. Maros is:1) In the game of dragon snakes, SD students implement the values of divinity, humanity, democracy, cooperation, unity, 2) At the games of the SD students implement the values of sportivity, honestly follow all the rules applied in the game, the attitude of willingness to acknowledge the defeat and superiority of the opponent player. 3) On the run game of the beam Pancasila's found values are the values of a player's sportivity to win a match, honesty, also fostering a sense of solidarity between players. 4) Pancasila's values found in the cat-cat game are the values of cooperation, the value of solidarity to each other's players, the Values of honesty, and also the training of discipline. All the values of Pancasila implemented in the four traditional games above will help to strengthen the personality and character of the students of SD Neg. 137 Inpres Kaemba Kab. Maros as the successor generation of the nation.